Plyometric Training Combinations with Mobilization with Movement Better Compared with Plyometric Training Combination with Strain Counter Strains in Improving Balance in The Chronic Ankle Instability in Barito Farma Clinic - Arfian Hamzah; Enny Fauziah; Tri Wahyu Wulandari (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2020)
ABSTRACT Chronic Ankle Instability (CAI) is a condition in which lateral ankle instability occurs such as pain and limited area of ​​joint motion after repeated injuries to the lateral ankle ligament. This study is to compare the combination of plyometric training with Mobilization with Movement (MWM) and the combination of plyometric training with Strain Counter Strain (SCS) to improve balance in the case of CAI. This research is an experimental study with a pre-test and post-test group design research design. The sample consisted of 22 people consisting of 11 people in each group. Group 1 was given plyometric training and MWM and group 2 was given plyometric training and SCS. Exercise is given 3 times a week for 6 weeks. The sampling technique was random sampling. Balance is measured by the Star Excursion Balance Test (SEBT). Paired sample t-test in both groups showed significant results for SEBT (p = 0.001). The results of the Independent sample t-test were SEBT values ​​(p = 0.001). The combination of plyometric training with MWM and the combination of plyometric training with SCS both improve balance. However, the combination of plyometric training with MWM is better than the combination of plyometric training with strain counterstrain in improving balance in cases of chronic ankle instability. Keyword: Mobilization with movement, Strain counter strain, Star excursion balance test, Chronic ankle instability